Environmental Development Communication and Social Impact from an Islamic Perspective - Muhammad Azwar; Zainun Zainun (Feedback International Journal of Communication, 2026)
Many environmental development programs generate various social impacts, including social conflict, inequality, and low public awareness of environmental risks. These problems often arise due to weak development communication practices that are still dominated by top-down approaches and limited community participation. Therefore, effective development communication is needed to build public awareness, participation, and responsibility in environmental management. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with development practitioners, community members, religious leaders, and academics, supported by observation and literature review. The data were analyzed using thematic analysis to identify patterns of communication in environmental development, the resulting social impacts, and the integration of Islamic values in development communication practices. Data validity was ensured through triangulation of sources, techniques, and theoretical perspectives. The results show that weak and non-participatory development communication can increase social vulnerability, reduce community preparedness in facing environmental risks, and potentially create social tensions within communities. In contrast, communication that is participatory, dialogical, and transparent can strengthen public understanding, increase community involvement, and support the sustainability of environmental development programs. From an Islamic perspective, environmental development communication is not only a technical process of information dissemination but also a moral responsibility related to the human role as khalifah fi al-ardh.